Living the audio life : a guide to a career in live entertainment audio - Schiller, Brad (London Routledge, 2022)
"Living the Audio Life details the aspects and procedures necessary for one to have a successful career in live entertainment sound. Encompassing a wide range of topics, the text clearly guides anyone interested in working and position within the live entertainment audio field. The guide is broken into clearly defined sections allowing the reader to easily navigate through various subjects including jobs, career, business, creativity, lifestyle, and travel. Real world examples and documentation from the author and key industry experts allow the reader to gain insight into essential practices helpful throughout a career. Additional in-depth interviews provide details of careers from industry veterans. Whether considering a career in live entertainment audio or just starting out, readers will find the resources within key to success in audio. Students, those new to sound, and workers already within their career can refer to the text as a guide throughout their journey. With benefits to anyone interested in the audio field, Living the Audio Life is a key navigational resource for success"--
Includes bibliographical references and index.
Keywords: Sound; Theaters; Sonic interaction design; Acoustical engineering; Sound engineers